Prevalence of missed lesions in patients with inadequate bowel preparation through a very early repeat colonoscopy. Issue 6 (8th April 2022) - Pantaleón Sánchez, Miguel; Gimeno Garcia, Antonio‐Z; Bernad Cabredo, Belen; García‐Rodríguez, Ana; Frago, Santiago; Nogales, Oscar; Diez Redondo, Pilar; Puig, Ignasi; Romero Mascarell, Cristina; Romero Sánchez‐Miguel, Ivan; Caballero, Noemí; Ibañez, Ines; et al.
Abstract : Objectives: When bowel preparation (BP) is inadequate, international guidelines recommend repeating the colonoscopy within 1 year to avoid missing clinically relevant lesions. We aimed to determine the rate of missed lesions in patients with inadequate BP through a very early repeat colonoscopy with adequate BP. Methods: Post hoc analysis was conducted using data collected from a prospective multicenter randomized clinical trial including patients with inadequate BP and then repeat colonoscopy. Inadequate BP was defined as the Boston Bowel Preparation Scale (BBPS) score <2 points in any segment. We included patients with any indication for colonoscopy. The adenoma detection rate (ADR), advanced ADR (AADR), and serrated polyp detection rate (SPDR) were calculated for index and repeat colonoscopies. Results: Of the 651 patients with inadequate BP from the original trial, 413 (63.4%) achieved adequate BP on repeat colonoscopy. The median interval between index and repeat colonoscopies was 28 days. On repeat colonoscopy, the ADR was 45.3% (95% confidence interval [CI] 40.5–50.1%), the AADR was 10.9% (95% CI 8.1–14.3%), and the SPDR was 14.3% (95% CI 10.9–17.7%). Cancer was discovered in four patients (1%; 95% CI 0.2–2.5%). A total of 60.2% of all advanced adenoma (AA) were discovered on repeat colonoscopy. A colon segment scored BBPS = 0 had most AA (66.1%) and all four cancers. Conclusion: Patients with inadequate BP present a high rate of AAs on repeat colonoscopy. When a colonoscopy has a colon segment score BBPS = 0, we recommend repeating the colonoscopy as soon as possible.